CULTURAL AND STYLISTIC ADAPTATION IN THE TRANSLATION OF IAN FLEMING‘S WORKS INTO UZBEK: CHALLENGES AND STRATEGIES (TAMADDUN NURI JURNALI, 2025)
This article examines the cultural and stylistic challenges encountered when translating Ian Fleming‘s works into Uzbek. Given the distinct linguistic structures and cultural references in Fleming‘s novels, translators often employ various strategies to ensure both accuracy and readability. The study highlights key translation techniques such as localization, compensation, and omission, demonstrating how they impact the target text’s fluency and authenticity.